Impact of Enrichment and Repeated Mixing on Resilience in Pigs - Luo, Lu; Zande, Lisette E. van der; Marwijk, Manon A. van; Knol, Egbert Frank; Rodenburg, T. Bas; Bolhuis, J. Elizabeth; Parois, Severine P. (Frontiers in Veterinary Science, 2022)
Resilience may be improved by enrichment, but negatively impacted by a high allostatic load from stressful management procedures in pigs. We investigated the combined effects of diverging environmental conditions from weaning and repeated mixing to create high allostatic load on resilience of pigs. Pigs were either exposed to barren housing conditions (B) from weaning onwards or provided with sawdust, extra toys, regular access to a ‘play arena’ and daily positive human contact (E). Half of the pigs were exposed to repeated mixing (RM) and the other half to one mixing only at weaning (minimal mixing, MM). To assess their resilience, the response to and recovery from an LPS challenge and a Frustration challenge were studied. In addition, potential long-term resilience indicators, e.g. natural antibodies, hair cortisol and growth were measured. Some indications of more favourable responses to the challenges in E pigs were found, such as lower serum dROM concentrations and smaller area under the curve of dROM after LPS injection; and, in the Frustration challenge, less standing alert, escape behaviours and other negative behaviours, a tendency for a smaller area under the curve of salivary cortisol and a lower plasma level at 1 h after the challenge. Aggression did not decrease over mixings in RM pigs and was higher in B pigs than in E pigs. Repeated mixing did not seem to reduce resilience. Contrary to expectations, RM pigs gained relatively more weight than MM pigs during the experiment, especially in the week of the challenges. B-RM pigs showed a lower plasma cortisol concentration than B-MM pigs after the LPS challenge, which may suggest that B-RM pigs responded less detrimentally than B-MM pigs. E-RM pigs showed a higher level of KLH-IgM than E-MM and B-RM, and RM pigs showed a sharper decline in PC-BSA-IgG over time than MM pigs. Hair cortisol concentrations were not affected by enrichment or mixing. To conclude, enrichment did not enhance the speed of recovery from challenges in pigs, although there were indications of reduced stress. Repeated as opposed to single mixing did not seem to aggravate the negative effects of barren housing on resilience.